Systematic Review and Meta-Analysis of Congenital Toxoplasmosis Diagnosis: Advances and Challenges - Priscila Silva Franco; Ana Carolina Morais Oliveira Scussel; Rafaela José Silva; Thadia Evelyn Araújo; Henrique Tomaz Gonzaga; Camila Ferreira Marcon; Joaquim Pedro Brito-de-Sousa; Angélica Lemos Debs Diniz; Marina Carvalho Paschoini; Bellisa Freitas Barbosa; Olindo Assis Martins-Filho; José Roberto Mineo; et al. (Journal of Tropical Medicine)
Objective. To understand how congenital toxoplasmosis (CT) diagnosis has evolved over the years, we performed a systematic review and meta-analysis to summarize the kind of analysis that has been employed for CT diagnosis. Methods. PubMed and Lilacs databases were used in order to access the kind of analysis that has been employed for CT diagnosis in several samples. Our search combined the following combining terms: “congenital toxoplasmosis” or “gestational toxoplasmosis” and “diagnosis” and “blood,” “serum,” “amniotic fluid,” “placenta,” or “colostrum.” We extracted data on true positive, true negative, false positive, and false negative to generate pooled sensitivity, specificity, and diagnostic odds ratio (DOR). Random-effects models using MetaDTA were used for analysis. Results. Sixty-five articles were included in the study aiming for comparisons (75.4%), diagnosis performance (52.3%), diagnosis improvement (32.3%), or to distinguish acute/chronic infection phases (36.9%). Amniotic fluid (AF) and placenta were used in 36.9% and 10.8% of articles, respectively, targeting parasites and/or T. gondii DNA. Blood was used in 86% of articles for enzymatic assays. Colostrum was used in one article to search for antibodies. In meta-analysis, PCR in AF showed the best performance for CT diagnosis based on the highest summary sensitivity (85.1%) and specificity (99.7%) added to lower magnitude heterogeneity. Conclusion. Most of the assays being researched to diagnose CT are basically the same traditional approaches available for clinical purposes. The range in diagnostic performance and the challenges imposed by CT diagnosis indicate the need to better explore pregnancy samples in search of new possibilities for diagnostic tools. Exploring immunological markers and using bioinformatics tools and T. gondii recombinant antigens should address the research needed for a new generation of diagnostic tools to face these challenges.